Depth versus subdural temporal electrodes revisited: Impact on surgical outcome after resective surgery for epilepsy. Issue 3 (March 2017) - Valentín, A.; Hernando-Quintana, N.; Moles-Herbera, J.; Jimenez-Jimenez, D.; Mourente, S.; Malik, I.; Selway, R.P.; Alarcón, G.
Highlights: Depth and subdural electrodes are effective for presurgical assessment of temporal lobe epilepsy. No differences in long term follow up were seen between patients with depth or subdural electrodes. In our series, depth electrodes showed lower complication rates. Abstract: Objective: To study retrospectively the impact of electrode modality (subdural or depth electrodes) during presurgical assessment on surgical outcome after temporal lobectomy. Methods: The study included 17 patients assessed with depth electrodes and 57 with bitemporal subdural strips. Results: MRI showed a larger proportion of bilateral pathology in patients undergoing depth recordings (29.41% versus 3.5%, p  = 0.00069). Among the operated patients, those undergoing depth electrode recordings showed better outcome at one year after surgery (11/12 versus 22/33; p  = 0.046). This difference disappears at longest follow up (10/12 versus 22/33; p  = 0.138). Moreover, the probability of undergoing surgery and having good outcome after assessment with intracranial recordings is higher for the depth electrode group at one-year follow up (11/17 versus 22/57; p  = 0.029) but statistical differences decrease to a trend for the longest follow up (10/17 versus 22/57; p  = 0.069). No other statistical differences were noted between subdural and depth electrodes. Depth electrodes showed lower complication rates than subdural electrodes. Conclusion: Both depth and subdural electrodes are effective for presurgical assessment of temporal lobe epilepsy. Significance: Assessment with depth electrodes is associated with slightly increased likelihood of surgery and marginally better surgical outcome at one year follow up which disappears for longer follow up periods. Initial assessment with depth electrodes would have avoided a second implantation in 15% of patients.